2019
DOI: 10.1021/acs.biochem.9b00541
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of FERM-Mediated Autoinhibition in Pyk2 Tyrosine Kinase

Abstract: Pyk2 is a non-receptor tyrosine kinase that evolved from gene duplication of focal adhesion kinase (FAK) and subsequent functional specialization in the brain and hemopoietic cells. Pyk2 shares a domain organization with FAK, with an N-terminal regulatory FERM domain adjoining the kinase domain. FAK regulation involves integrin-mediated membrane clustering to relieve autoinhibitory interactions between FERM and kinase domains. Pyk2 regulation remains cryptic, involving Ca2+ influx and protein scaffolding. Whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Beyond epitope mapping, HDX-MS continues to be utilized for studying protein–protein interactions in complex protein systems and revealing mechanisms of activation in a range of systems including: clotting factors, , metabolic enzymes, ,, heat shock proteins ,, and other chaperones, signaling complexes, and complexes exclusively residing in membranes . HDX-MS has also been extensively used to study interactions between proteins with nucleic acids, including activation of transcription factors. Other notable applications are the characterization of ligands with weak affinity such as metals , or carbohydrates. , For proteins with multiple distinct ligand binding sites, it has been shown that by performing a concentration series it is possible to characterize individual interactions. , The strength of HDX-MS to provide detailed insight into such a wide range of interactions continues to drive its use to study increasingly complex biological systems.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…Beyond epitope mapping, HDX-MS continues to be utilized for studying protein–protein interactions in complex protein systems and revealing mechanisms of activation in a range of systems including: clotting factors, , metabolic enzymes, ,, heat shock proteins ,, and other chaperones, signaling complexes, and complexes exclusively residing in membranes . HDX-MS has also been extensively used to study interactions between proteins with nucleic acids, including activation of transcription factors. Other notable applications are the characterization of ligands with weak affinity such as metals , or carbohydrates. , For proteins with multiple distinct ligand binding sites, it has been shown that by performing a concentration series it is possible to characterize individual interactions. , The strength of HDX-MS to provide detailed insight into such a wide range of interactions continues to drive its use to study increasingly complex biological systems.…”
Section: Current Uses Of Hdx-msmentioning
confidence: 99%
“…This shared structural composition results in a significant similarity in the activation mechanisms and biological functions of PYK2 and FAK. Indeed, both proteins have an autoinhibited conformation in which the FERM domain binds to the kinase domain, thereby inhibiting its catalytic function 17 , 18 . The activation of kinase-dependent functions requires ligand-induced self-association (dimerisation or clustering) to trigger autophosphorylation in trans of a pivotal tyrosine (Y397 in FAK and Y402 in PYK2).…”
Section: Introductionmentioning
confidence: 99%
“…Pyk2 activity is silenced through autoinhibition of the kinase domain by the N-terminal four band−ezrin−radixin−moesin (FERM) domain, and Pyk2 autoinhibition state could be relieved by autophosphorylation activity mediated by the tyrosine residue at the 402 position (Y402) ( Eide et al, 1995 ; Lev et al, 1995 ; Dikic et al, 1996 ; Girault et al, 1999 ; Park et al, 2004 ). Autophosphorylation of the Pyk2 Y402 site induces a conformational change and relieves the blocking of the kinase domain by FERM ( Lietha et al, 2007 ; Han et al, 2009 ; Loving and Underbakke, 2019 ). Autophosphorylated Pyk2 then recruits c-Src through docking on the phosphorylated Y402 site via the c-Src SH2 domain ( Dikic et al, 1996 ; Lakkakorpi et al, 2003 ; Park et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%